Vinclozolin-induced mouse penile malformation and "small testis" via miR132, miR195a together with the Hippo signaling pathway. (August 2021) - Yu, Haiming; Yang, Jinru; Zhang, Yujing; Fu, Hu; Yan, Zhengli; Zhu, Yongfei
Abstract: Vinclozolin (VCZ) is a fungicide with antiandrogen activity. Exposure to VCZ in maternal uterus may cause uterine, ovarian and testicular damage, hypospadias and prostate abnormality in the offspring. Hippo pathway, which is highly conservative and may be activated by miR132 and miR195a, can control organ size and tissue regeneration, and participate in injury and deformity. In the present study, VCZ was found to have caused penile malformation in the male offspring and also induced "small testis" when it was administered to the pregnant mice orally at a dose of 400 mg kg −1 day −1 on Days 12–18 of gestation. At 1, 3 and 7 weeks of age, VCZ could increase miR132, Mst1, Sav1, phosphorylated Yes-associated protein (pYap) and pLats, and decrease Yap in offspring penises and testes. Besides, it could also raise miR195a both in the testes of 1, 7-week and in the penises of all the three ages. In addition, we found the levels of some cyclin (Ccn) genes elevated in the testes, the expression of the androgen receptor (Ar) gene dereased and Jnks changed in the penises of offspring aged 1, 3 and 7 weeks. The results suggest that that gestational VCZ exposure could not only increase miR132 and miR195a in penises and testes of the offspring, but also activate Hippo pathway and down-regulate Ar . These may directly inhibit cell proliferation, accelerate cell death by up-regulating the expression of some Ccns, and ultimately lead to penile and testicular damage and malformations in the offspring.